2005
DOI: 10.1124/jpet.105.094276
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Antinociceptive Response to Morphine and Morphine-Like Compounds in Male and Female Sprague-Dawley Rats

Abstract: Male rats are more sensitive to the antinociceptive effects of morphine than female rats. This difference is seen across several rat strains using a variety of nociceptive stimuli. However, the literature in regard to sex differences in antinociceptive responses to -opioids other than morphine is less consistent. The present study was designed to examine whether there is a structure-activity rationale that determines which -opioids will show a differential antinociceptive response between male and female rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 25 publications
3
119
1
2
Order By: Relevance
“…Women exhibit enhanced sensitivity to experimental pain (for review, see Fillingim and Maixner, 1995) and experience a greater prevalence of pain disorders (Fillingim and Maixner, 1995) (for review, see Berkley, 1997). Sex-related differences in pain modulation by activation of G-proteincoupled receptors such as opioid ( and ) and ␣ 2 noradrenergic receptors have been demonstrated in human and animal studies (Gear et al, 1996;Mitrovic et al, 2003;Mogil et al, 2003;Fillingim and Gear, 2004;Nag and Mokha, 2006;Peckham and Traynor, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Women exhibit enhanced sensitivity to experimental pain (for review, see Fillingim and Maixner, 1995) and experience a greater prevalence of pain disorders (Fillingim and Maixner, 1995) (for review, see Berkley, 1997). Sex-related differences in pain modulation by activation of G-proteincoupled receptors such as opioid ( and ) and ␣ 2 noradrenergic receptors have been demonstrated in human and animal studies (Gear et al, 1996;Mitrovic et al, 2003;Mogil et al, 2003;Fillingim and Gear, 2004;Nag and Mokha, 2006;Peckham and Traynor, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that these MOR agonists and metabolites have interesting pharmacological differences (Peckham and Tratnor, 2006;Lemberg et al, 2006a, b). Oxycodone has been in clinical use since 1917.…”
Section: Introductionmentioning
confidence: 99%
“…log P [149,150] (octanol-water) A. G. Asimakopoulos and K. Kannan compounds in untreated wastewater and during wastewater treatment. [10] Glucuronidated morphine has been detected in wastewater influent at low concentrations (2-18 ng L À1 ), demonstrating the cleavage of the glucuronide bond in wastewater treatment processes.…”
Section: Chemicalmentioning
confidence: 99%
“…Methadone is also prescribed for patients in substance-abuse programs and has a readily quantifiable metabolite, 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) ( Table 1). [23,28,30,31] Morphine is excreted in urine as morphine-3b-D-glucuronide and morphine6b-D-glucuronide or as free morphine. [10] Codeine is excreted in urine mainly (,70 %) as codeine-6-glucuronide.…”
Section: Opioidsmentioning
confidence: 99%